2012
DOI: 10.3892/ijmm.2012.1122
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin-D9k as a sensitive molecular biomarker for evaluating the synergistic impact of estrogenic chemicals on GH3 rat pituitary cells

Abstract: Various endocrine-disrupting chemicals (EDCs) such as bisphenol A (BPA), alkylphenols [4-nonylphenol (NP) and 4-tert octylphenol (OP)] and isobutylparaben (IBP) are a constant concern due to their widespread distribution. It has been reported that some combinations of hormone-disrupting chemicals are much more powerful than any of the chemicals alone. In this study, we measured the expression of an estrogenic biomarker gene, calbindin-D9k (CaBP-9k), and progesterone receptor (PR) to evaluate the individual or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Evidences have shown that ligand-activated ERs positively or negatively modulate gene transcription via binding to the specific ERE within their target genes [23]. For example, E2 was shown to increase prolactin transcription through ERE which is located upstream of the 5 -regulatory region of prolactin [24,25]. Coincidentally, CaBP-9k promoter also contains the minimal ERE at nucleotides +51 to +61, which was able to bind to ERα [26].…”
Section: Discussionmentioning
confidence: 99%
“…Evidences have shown that ligand-activated ERs positively or negatively modulate gene transcription via binding to the specific ERE within their target genes [23]. For example, E2 was shown to increase prolactin transcription through ERE which is located upstream of the 5 -regulatory region of prolactin [24,25]. Coincidentally, CaBP-9k promoter also contains the minimal ERE at nucleotides +51 to +61, which was able to bind to ERα [26].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, total RNA (1 µg) was reverse transcribed into complementary DNA (cDNA) using M-MLV reverse transcriptase (Invitrogen) and a random primer (9-mer; Takara Bio, Inc., Shiga, Japan). The cDNA (1 µl) was used for PCR under standard conditions (13,16); denaturation at 95˚C for 30 sec, annealing at 55˚C for 30 sec and extension at 72˚C for 1 min. The primer sequences used were as follows: COX-2 sense, 5'-TACCCGGACTGGATTCTACG-3' and antisense, 5'-AAGTTGGTGGGCTGTCAATC-3'; TNFα sense, 5'-CTGAGCTCAAGCCCTGGTAT-3' and antisense,…”
Section: Peripheral Blood Mononuclear Cell (Pmnc) Isolationmentioning
confidence: 99%
“…2-ME was applied to GH3 cells at three concentrations (10 -8 , 10 -7 and 10 -6 M). CaBP-9k mRNA levels were then analyzed as an estrogen marker of rat pituitary GH3 cells using RT-qPCR (25). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The estrogenic or non-estrogenic activity of estrogen metabolites and EDs has been evaluated in recent studies (25,26). However, the residual effect of high dose 2-ME administered to cancer patients on physiological conditions remains to be fully elucidated.…”
Section: Two Faces Of the Estrogen Metabolite 2-methoxyestradiol In Vmentioning
confidence: 99%